Students' engagement in 'design thinking' for school innovation programme : a case study of SBPI Gombak - Nazatul Syirin Mohammad Mokhtar (Kulliyyah of Education, International Islamic University Malaysia, 2021)
The main objective of this research is to study students' level of thinking in posing questions for design thinking process. The other objective is to explore students' level of creativity in developing a draft prototype. In addition, this study also explores students' perceptions in design thinking programme. This research used purposive sampling. Twenty students aged thirteen and fourteen from Sekolah Berasrama Penuh Integrasi Gombak were chosen to conduct this research. The data collected through three aspects which are interview, observation and reflection. The interview data are then synthesized to understand better. The overall analysis indicates that students in SBPI Gombak were still not fully understand the design thinking process. From observation, teachers are more concern on teaching subject rather than allowing students to develop their creative thinking. Students' level of creativity can be reinforced if the group size is limited to six or fewer. Creativity of students is not achievable in design thinking process because students do not know which step to be used or in what situation should be used. It is also found that students got demotivated to integrate design thinking in their learning because of heavy school work load and syllabus